MODEL PBL BERBANTUAN MEDIA KOKAMI UNTUK MENINGKATKAN HOTS PADA MATERI BUMI DAN TATA SURYA - Astutik, Sri; Hartiningsih, Try; Ahied, Mochammad; Wulandari, Ana Yuniasti Retno; Rais, M. Amien (Natural Science Education Research, 2025)
This study was conducted because students' HOTS is still relatively low because students are still unable to follow the HOTS learning pattern. The purpose of this study was to determine the increase in students' HOTS after the application of the PBL model assisted by KOKAMI media on the Earth and Solar System material. This study used a quasi-experimental design method and was carried out at SMPN 1 Pasean. The study population was all grade VII students in the 2024/2025 Academic Year. Sampling used a purposive sampling technique. The sample used was class VII-A. The analysis technique for increasing students' HOTS used the N-gain test. The results of the study showed that there was an increase in students' HOTS after the application of the PBL model assisted by KOKAMI with an average n-gain result of 0.71 in the high category.